The genre resource of the fable in the literature of Russian futurism - Ternova, Tatiana (Przegląd Wschodnioeuropejski, 2018)
The article deals with the artistic possibilities of the fable genre in the work of Russian futurists. Wanting to transform the principles of the world order in general, the representatives of the current naturally drew attention to the existing system of genres, which they perceived not only as an element of the culture of the past, but also as an expression of a worldview that lost its connection with reality. The genre of the fable is in demand among the futurists precisely because it lies almost outside the genre system of high literature. In the work of V. Khlebnikov, A. Kruchenykh, V. Mayakovsky, the fable is endowed with additional tasks, fulfilling the role of a parable (Khlebnikov), a pamphlet and an advertising text (Mayakovsky). The text of A. Kruchenykh “Sobasnya”, having an original title, exemplifies, inherent in the transitional era, of the idea of updating the genre.